Predicting initiation of preventive migraine medications: exploratory study in a large U.S. medical claims database. (2nd January 2020) - Ford, Janet H.; Schroeder, Krista; Buse, Dawn C.; Joshi, Shivang; Gelwicks, Steven; Foster, Shonda A.; Aurora, Sheena K.
Abstract: Objective: Despite guidelines that identify potential patients eligible for preventive migraine medications, their underutilization leaves patients at risk of acute medication overuse, disease progression, and higher healthcare resource utilization and disability. This exploratory, retrospective, observational study aimed to identify which factors predict preventive migraine medication initiation. Demographics and initiation of acute medication use were hypothesized to be predictive of initiation of preventive migraine medication. Methods: The Truven Health Analytics MarketScan 1 U.S. Commercial and Medicare Supplemental claims database (2011-2013) was used to identify adults newly diagnosed with migraine. Patients were divided into 2 subgroups: initiated a preventive migraine medication (antidepressants, anti-epileptics, beta-blockers, or neurotoxins) within 1 year of migraine diagnosis and did not initiate a preventive migraine medication. Logistic regression models were constructed to identify factors associated with preventive migraine medication initiation. Results: Study population included 147, 923 patients: 43, 660 preventive migraine medication initiators and 104, 263 non-preventive migraine medication patients. Best-fit model for predicting preventive migraine medication initiation included: female gender (odds ratio = 1.181 [95% CI = 1.144, 1.218]; measured at date of first migraine diagnosis); headache diagnosis prior to migraine diagnosis (odds ratio = 1.538 [95% CI = 1.498, 1.579]; measured 1-year before first migraine diagnosis); and sleep disorder (odds ratio = 1.206 [95% CI = 1.161, 1.252]), headache/migraine-specific Emergency Department (ED) visit (odds ratio = 1.224 [95% CI = 1.168, 1.283]), neurologist visit (odds ratio = 1.502 [95% CI = 1.459, 1.547]), and acute medication refills with <90-day gap (odds ratio = 1.509 [95% CI = 1.470, 1.549]) each measured at 1-year before first preventive migraine medication. Conclusions: In addition to consistent acute medication refills, specific comorbidity diagnoses, headache/migraine-specific ED utilization, and neurologist care are predictive of preventive migraine medication initiation in the 1-year post-incident migraine diagnosis.